An Investigation of EFL Students' Perception of Integration Between Morphology and Pronunciation in The English Language - Mahmoud, Salma Turki; Sultan, Amra Ibrahim (Journal of Tikrit University for Humanities, 2023)
The study aims to investigate the students' perception the integration between morphology and pronunciation in the English language. The problem of the study is that English language students study the change of pronunciation additions according to the laws of sound at the secondary stage, but at the university stage, despite their study of phonetics and phonology, the degree of their awareness of the overlap between morphology and phoneme is unknown. The study sample consists of (150) samples, including (90) males and (60) females. The results of the study shows that the students got a medium mark of perception the integration between morphology and pronunciation in the English language. According to the findings and results of the study it has been noticed that the ability of male and female students in morphological and phonological levels, are not equal. where the performance of the male students is better than the females in the diagnostic test. In this case the hypothesis which states that there is significant difference between the male and female students' level is accepted. Also, the results of the questionnaire show that the students' perception of integration is not good, as they do not realize the relationship between the two, and even they seem unaware of the teaching relationship at this stage, which increases the students' ability to interact, and the students are not aware of the vocabulary of the paragraphs mentioned in the questionnaire.